RU.521 protects against neutrophil extracellular traps-induced vascular endothelial injury by inhibiting cGAS/STING pathway - Biao Zhang; Zaojun Fang; Ying Lin; Qian Wu; Jiaping Chen (Bangladesh Pharmacological Society, 2024)
This study aims to investigate the effect of RU.521 on improving vascular endothelial injury in 14 acute lung injury patients. Serum myeloperoxidase, double-stranded DNA (dsDNA), IFN-β, and TNF-α levels of patients were detected by ELISA. Neutrophil extracellular traps were used to stimulate human venous endothelial cells (HUVEC). cGAS/STING pathway protein was detected by western blot. The protective effect of RU.521 on HUVEC was evaluated by CCK-8. The effects of RU.521 on cGAS/STING pathway expression were detected by PCR and western blot. The levels of myeloperoxidase and (dsDNA) in acute lung injury patients were significantly increased (p<0.05). The expression level of IFN-β in acute lung injury patients was significantly increased (p<0.05). The expression of cGAS and STING proteins in HUVEC cells was significantly increased (p<0.05), and the expression of IFN-β was significantly increased (p<0.05). RU.521 can ameliorate vascular endothelial injury. RU.521 inhibited cGAS/SRING mRNA and protein expression (p<0.05). Thus, neutrophil extracellular traps release dsDNA activates the cGAS/STING pathway-induced vascular endothelial injury in acute lung injury patients. RU.521 protects vascular endothelial injury by inhibiting the cGAS/STING pathway.